PENGARUH PENERAPAN BAHAN AJAR BERBASIS KARAKTER MELALUI MODEL PEMBELAJARAN CONTRUCTIVE CONTROVERSY TERHADAP HASIL BELAJAR SISWA KELAS XI SMAN 6 PADANG - Nadya Yunestika; Yenni Darvina; Masril Masril (Universitas Negeri Padang, 2015)
The results of student learning in physics have not achieved well. Caused less motivated students in learning, teaching models and instructional materials used are less varied yet contain character values. Researchers apply a character-based teaching materials with learning model contructive controversy. The goal is to investigate the effect of the application of character-based teaching materials through learning model contructive controversy to the learning outcomes of students of class XI SMAN 6 Padang. The research is a Quasi-Experiment Research with Randomized Control Group Only Design. The study population was a class XI student of SMAN 6 Padang listed in the Academic Year 2014/2015. The research data include student achievement on the competence of knowledge, attitudes, and skills were analyzed using t-test. Average values obtained for the third class of experiments on competence higher than the control class. Thus an acceptable working hypothesis at the 95% confidence lev